Disparities in prevalence of screening/monitoring in children with intellectual and developmental disabilities: culturally sensitive provider can mitigate effects - Mudnal, Purnima S.; Chuang, Emmeline; Needleman, Jack; Rosenau, Kashia; Kuo, Alice A. (Frontiers in Education, 2024)
More than one in six children in the U.S., about 17% of the population, have one or more intellectual or developmental disabilities (IDD), or conditions that may impair their physical activity, learning, language, or behavior (Cogswell et al., 2022). Some examples of these conditions include attention-deficit/hyperactivity disorder, autism spectrum disorder, blindness, cerebral palsy, moderate to profound hearing loss, learning disability, seizures, stuttering or stammering, and or without intellectual impairment (Hotez et al., 2021). The number of children with physical or neurodevelopmental disabilities in the U.S. has increased over the last decade; in particular, increases in disability due to neurodevelopmental or mental health conditions have increased by 20.9% (Houtrow et al., 2014).